Removal of pharmaceuticals from municipal wastewater using Malaysian Ganoderma lucidum fungal strain - Khalid Sayed; Wan Hanna Melini Wan Mohtar; Zarimah Mohd Hanafiah; Aziza Sultana Bithi; Wan Abd Al Qadr Imad Wan-Mohtar (Penerbit Universiti Kebangsaan Malaysia, 2024)
Emerging contaminants are currently a serious issue primarily because conventional wastewater treatment plants are unable to eliminate them. Environmental pollution caused by various emerging pollutants (particularly pharmaceutical active compounds) in wastewater poses a significant threat to public health and ecological balance. In 21st century, bioremediation is regarded as the most environmental friendly and cost-effective treatment technology. In this study, we investigated the removal efficiency of 19 popular pharmaceutical active compounds (PhACs) from municipal wastewater using Malaysian Ganoderma lucidum fungal strain (G. lucidum). The initial and final concentrations of each compound were determined using liquid chromatography time of flight mass spectrometry (LC-TOF/MS), and the percentage of removal was calculated. In this study, experimental results revealed diverse removal efficiencies for the investigated PhACs in municipal wastewater. The PhACs Azithromycin, doxycycline, clindamycin, ciprofloxacin, sulfamethoxazole, loratadine, and citalopram, showed remarkable removal rates of 90% and above in municipal wastewater, indicating their potential for effective treatment. Conversely, trimethoprim, ketoprofen, diclofenac, venlafaxine, dexamethasone, atenolol, propranolol, losartan, valsartan, metoprolol, fluconazole, and carbamazepine, demonstrated varying removal efficiencies, suggesting the need for further optimization in wastewater treatment processes for these compounds. This study highlights the importance of understanding the biodegradation of different PhACs in municipal wastewater to develop efficient and targeted bioremediation treatment strategies using local fungal strain of G. lucidum. Overall, this study provides promising suggestions for the bioremediation of pharmaceuticals from wastewater.